2009
DOI: 10.1007/s00704-009-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

On the 60-month cycle of multivariate ENSO index

Abstract: Many point indices have been developed to describe El Niño/Southern Oscillation but the Multivariate El Niño Southern Oscillation (ENSO) Index (MEI) is considered the most representative since it links six different meteorological parameters measured over the tropical Pacific. Spectral analysis with appropriate data reduction techniques of monthly values of MEI (1950-2008) has allowed the identification of a large 60-month cycle, statistically confident at a level larger than 99%. The highest values of MEI (ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…Pattern of PC1 correlation with SST shows correlations in the eastern Indian Ocean and western Pacific (Figure 6a), however the correlation is not significant after detrend. PC2 shows a positive yet insignificant correlation with the El Niño-Southern Oscillation (ENSO) pattern, similar to that found by Mazzarella et al [53], albeit weaker (Figure 6b). PC3 is related to reduced precipitation over the east coast of Tanzania (Figure 5c,g) in association with increased SST in the Arabian Sea and the western Pacific Ocean (Figure 6c).…”
Section: Variabilitysupporting
confidence: 84%
“…Pattern of PC1 correlation with SST shows correlations in the eastern Indian Ocean and western Pacific (Figure 6a), however the correlation is not significant after detrend. PC2 shows a positive yet insignificant correlation with the El Niño-Southern Oscillation (ENSO) pattern, similar to that found by Mazzarella et al [53], albeit weaker (Figure 6b). PC3 is related to reduced precipitation over the east coast of Tanzania (Figure 5c,g) in association with increased SST in the Arabian Sea and the western Pacific Ocean (Figure 6c).…”
Section: Variabilitysupporting
confidence: 84%
“…We found that the short periods (2-8 years) and medium periods (9-14 years) were mainly distributed in north Xinjiang. Mazzarella et al [50] found that multivariate El Niño Southern Oscillation (ENSO) index had a short period of 5 years. Their result was similar to a short period of snow depth.…”
Section: Spatiotemporal Variability Of Snow Depths In Xinjiangmentioning
confidence: 99%
“…The values of A/vpe ratio (Table 1) show that the 28-month harmonic is much more statistically significant inside the bin enclosed between 15 and 40 hPa levels in respect to that enclosed between 40 and 70 hPa. Similar statistical analyses [21] applied to monthly series of Multivariate Enso Index (MEI) have allowed the identification of a quasi biennial harmonic at a level of confidence higher than 99%. Since the highest values of MEI represent El Niño events, the obtained results would suggest the strict relationship between El Niño and the equatorial stratospheric winds.…”
Section: Discussionmentioning
confidence: 99%